Leptin Gene Epigenetic Adaptation to Impaired Glucose Metabolism During Pregnancy - Bouchard, Luigi (American Diabetes Association, 2010)
OBJECTIVE: To verify whether the leptin gene epigenetic (DNA methylation) profile is altered in the offspring of mothers with gestational impaired glucose tolerance (IGT). RESEARCH DESIGN AND METHODS: Placental tissues and maternal and cord blood samples were obtained from 48 women at term including 23 subjects with gestational IGT. Leptin DNA methylation, gene expression levels, and circulating concentration were measured using the Sequenom EpiTYPER system, quantitative real-time RT-PCR, and enzyme-linked immunosorbent assay, respectively. IGT was assessed after a 75-g oral glucose tolerance test (OGTT) at 24–28 weeks of gestation. RESULTS: We have shown that placental leptin gene DNA methylation levels were correlated with glucose levels (2-h post-OGTT) in women with IGT (fetal side: ρ = −0.44, P ≤ 0.05; maternal side: ρ = 0.53, P ≤ 0.01) and with decreased leptin gene expression (n = 48; ρ ≥ −0.30, P ≤ 0.05) in the whole cohort. Placental leptin mRNA levels accounted for 16% of the variance in maternal circulating leptin concentration (P < 0.05). CONCLUSIONS: IGT during pregnancy was associated with leptin gene DNA methylation adaptations with potential functional impacts. These epigenetic changes provide novel mechanisms that could contribute to explaining the detrimental health effects associated with fetal programming, such as long-term increased risk of developing obesity and type 2 diabetes.